2019
DOI: 10.3389/fmicb.2019.01124
|View full text |Cite
|
Sign up to set email alerts
|

The Not-so-Sterile Womb: Evidence That the Human Fetus Is Exposed to Bacteria Prior to Birth

Abstract: The human microbiome includes trillions of bacteria, many of which play a vital role in host physiology. Numerous studies have now detected bacterial DNA in first-pass meconium and amniotic fluid samples, suggesting that the human microbiome may commence in utero . However, these data have remained contentious due to underlying contamination issues. Here, we have used a previously described method for reducing contamination in microbiome workflows to determine if there is a fetal bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
262
3
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(289 citation statements)
references
References 86 publications
4
262
3
6
Order By: Relevance
“…Whether there are microbiota (live or simply DNA signatures) in the maternal-fetal interface remains mired in controversy. In the recent years, there has been a large number of studies, providing both sequencing and histological evidence, indicating microbial signatures 3,11,18,19,22,23,29 , while other studies have reported these signatures as likely DNA contaminants originating from the sample collection and/or the DNA extraction process, rather than the placenta itself [54][55][56][57] . Placenta location remains a key variable in the aforementioned studies given that that BP, PV and FM have distinct physiology and function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether there are microbiota (live or simply DNA signatures) in the maternal-fetal interface remains mired in controversy. In the recent years, there has been a large number of studies, providing both sequencing and histological evidence, indicating microbial signatures 3,11,18,19,22,23,29 , while other studies have reported these signatures as likely DNA contaminants originating from the sample collection and/or the DNA extraction process, rather than the placenta itself [54][55][56][57] . Placenta location remains a key variable in the aforementioned studies given that that BP, PV and FM have distinct physiology and function.…”
Section: Discussionmentioning
confidence: 99%
“…These probes predominately bind to 16S rRNA and the bright staining suggests a large intact rRNA pool, which is typically a hallmark of viability. Finally, the guidelines suggest that it must be "ecologically plausible" for the detected microbes to reside in the placenta 3,58 . In this report, we show that R. insidiosa replicates within human placental samples, human BP explants cultured ex vivo, and EVT-like JEG-3 cells in culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, the foetus has been considered to exist in a sterile environment with initial microbial colonization of the newborn taking place during birth (51). Recent studies have reported the detection of microbes from amniotic fluid, placenta and meconium, suggesting that microbial colonization may begin in utero (52, 53). In addition, a number of studies have reported bacterial communities from meconium specimens (54).…”
Section: Discussionmentioning
confidence: 99%
“…This has led to discussion in the literature on the caveats associated with studies of the microbiota of very low microbial biomass, or potentially sterile, body sites (4754). In particular, there has been much debate over the existence of a placental microbiota (3145, 50, 5569) and of in utero microbial colonization of the human fetus (36, 4446, 64, 7072).…”
Section: Introductionmentioning
confidence: 99%